Analysis of treatment options and survival outcomes for patients with localized prostate cancer: a focus on androgen deprivation therapy - Li, Zhiqiang; Sun, Shiwei; Tan, Chenghao; Yan, Huwei; Zhang, Yali; Yang, Yingzhong; Xiong, Gengyan (Frontiers in Oncology, 2025)
BackgroundManagement of localized prostate cancer (PCa) remains challenging in resource-limited settings where access to surgery and radiotherapy is restricted. This study assessed the survival outcomes of patients receiving androgen deprivation therapy (ADT) alone compared with other modalities.MethodsWe retrospectively analyzed patients with localized PCa treated with ADT at Taiyuan Central Hospital of Shanxi Medical University from 2002 to 2023. Cox regression identified prognostic factors for overall survival (OS), disease-specific survival (DSS), and progression-free survival (PFS). Outcomes were compared with SEER database cohorts receiving radical prostatectomy (RP), radiotherapy (RT), or no treatment. Propensity score matching (PSM) was used to balance baseline characteristics.ResultsAmong 86 patients in the ADT cohort, the median follow-up was 2,152.5 days. Median OS was 2,378 days, with 5-year OS, DSS, and PFS rates of 58.4%, 85.2%, and 72.5%, respectively. Cox analysis identified prostate-specific antigen, ISUP grade, and body mass index as independent predictors of PFS. After PSM for age and ISUP grade, the ADT group showed significantly better OS and DSS than RP, RT, or no treatment cohorts in the SEER database.ConclusionsADT demonstrated favorable survival outcomes compared with RP and RT in elderly patients with high-grade localized PCa. These results highlight ADT as a potential alternative where invasive options are less feasible, providing insights into optimizing treatment strategies for resource-limited settings.